Edukasi Pengelolaan Keuangan Rumah Tangga Sebagai Upaya Meningkatkan Pemahaman Masyarakat Sibalaya Selatan - Puput Risna; Andi Herman Jaya; Yoberth Kornelius (Jurnal Nusantara Berbakti, 2023)
The community's low understanding of financial management means that financial management education is carried out which aims to provide understanding and knowledge about the importance of financial planning and how to allocate good expenditure items within the family environment. The method used in this education is the method of discussion and question and answer as an effort to find out the extent of knowledge of residents about their finances. The results of this education show an increase in public knowledge about managing their finances, before this education was carried out only some residents knew the ideal percentage of expenditure items in their family. then after educating the implementing party to evaluate it, it can be seen that there is an increase in residents' understanding of the ideal percentage for spending based on needs, wants and savings and the maximum debt they have.